Scanning Electron Microscopic Study of the Pancreas Gland of the Rabbit (Oryctolagus Cuniculus) and Guinea Pig (Cavia Porcellus): Comparative Study (Indian Journal of Animal Production and Management, 2025)
The pancreas is a vital organ with both endocrine and exocrine functions in  mammalian species. This report presents a comparative study of the ultrastructural  characteristics of pancreatic tissue in the rabbit (Oryctolagus cuniculus) and  guinea pig (Cavia porcellus) using scanning electron microscopy (SEM). Pancreas  specimens were obtained from healthy adult animals on the University of Muthanna  and processed for SEM using standard techniques for SEM processing. This study  has documented different sizes of acinar cells, ductal structure, and organization  of islets between the two species. The rabbit pancreas exhibited larger acini than  guinea pig pancreas with more larger zymogen granules than that in the guinea  pig. In contrast, the guinea pig pancreas exhibited more acinar units more densely  packed with smaller acinar and cellular dimensions. Additionally, the ductal system  of the rabbit pancreas exhibited more branching than that of the guinea pig pancreas.  The current study adds to our knowledge of comparative pancreatic morphology  to different species, regardless of physiological functional similarities, which has  intrinsic importance in future studies involving comparative physiology or as an  experimental model.
Keywords: Pancreas; SEM; Rabbits; guinea pig